Macroscopic Fundamental Diagram Approach to Evaluating the Performance of Regional Traffic Controls. Issue 7 (July 2020) - Lu, Weike; Liu, Jun; Mao, Jiannan; Hu, Guojing; Gao, Chuqiao; Liu, Lan
Evaluating a regional traffic control system requires understanding both the advantages and disadvantages of control schemes as well as the interrelated characteristics of the system. To assess the efficiency of regional signal control schemes in a road network, this study, which is based on the macroscopic fundamental diagram (MFD) concept, proposes four evaluative indicators: maximum throughput, critical accumulation, gridlock accumulation and the degree of homogeneity. The maximum throughput and gridlock accumulation can be used to reflect the road network capacity and load capacity, respectively. The degree of homogeneity quantifies the spatial variations of traffic flows in the network. Combined with the gridlock accumulation, the critical accumulation values the durability of a regional control system in managing congestion in the network. This study used the regional road network in Qingyang District of Chengdu, China, as a real-world example to demonstrate the proposed MFD-based approach. In the demonstration, the MFD-based evaluation method was compared to the traditional travel time-based method. The demonstration evaluated the control effect and characteristic values of the network under four control modes: fixed-time, actuated, adaptive and adaptive coordinated control.